Pengaruh Disiplin Kerja dan Komunikasi terhadap Kinerja Karyawan PT. Perusahaan Listrik Negara (PLN Persero) ULP Perbaungan - Shakila, Intan; Nasti, Nilawati; Pinem, M. Nelson (JRMB (Jurnal Riset Manajemen & Bisnis), 2023)
The aim of this research is to determine the effect of work discipline on employee performance at State Electric (PLN PERSERO) ULP Perbaungan. To find out the effect of communication on employee performance at State Electric (PLN PERSERO) ULP Perbaungan, to determine the effect of work discipline and communication on employee performance at the state electricity company (PLN PERSERO) ULP Perbaungan. The population and sample in this study were 69 people. Data collection technique use data quality test, classical assumption test, multiple linear analysis and hypothesis testing. The result of this research show that work discipline partially has a significant effect on employee performance. Communication partially has a significant effect on employee performance. Work discipline and communication simultaneously have a positive and significant effect on employee performance